2019
DOI: 10.24925/turjaf.v7i9.1310-1320.2533
|View full text |Cite
|
Sign up to set email alerts
|

Water-Yield Relationships in Deficit Irrigated Onion

Abstract: This trial was realized in the greenhouses of Uludağ University Yenişehir Vocational School between 2009 and 2010 to investigate effects of water deficit on yield and quality parameters of onion during four crop growth stages. In this trial, fourteen irrigation treatments in four growth periods (establishment, vegetative, yield formation and ripening) of onion (Allium cepa L E.T Grano.502) were constituted and the yield and quality parameters found from these treatments were evaluated. The layout of the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…and 0.0 g/l salicylic acid gave the highest values, but the lowest values were recorded with 1300 m 3 / fed. and 0.3 g/l salicylic acidThese results coincide with those reported by Ayas and Korukcu (2010)…”
Section: -Plant Water Relationssupporting
confidence: 91%
“…and 0.0 g/l salicylic acid gave the highest values, but the lowest values were recorded with 1300 m 3 / fed. and 0.3 g/l salicylic acidThese results coincide with those reported by Ayas and Korukcu (2010)…”
Section: -Plant Water Relationssupporting
confidence: 91%
“…Any recommended value of K for regional irrigation scheduling program must be high enough to prevent water stress arising from emergencies and specialized local situations, while remaining low enough for efficient water management (Yuan et al, 2003). Based on the US Weather Bureau Class A pan evaporation, many studies have been completed on the irrigation of cabbage (Kiziloglu et al, 2008), broccoli (Ayas et al, 2011), tomato (Ayas, 2015); green bean (Büyükcangaz et al, 2008); pepper (Demirtas and Ayas, 2009), cucumber (Ayas and Demirtas, 2009), lettuce (Yazgan et al, 2008) and potato (Ayas and Korukcu, 2010;Ayas, 2013). Several studies have been performed to investigate the influence of different irrigation levels on cabbage growth and yield.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that the percentage of dry matter of the tubers increases with decreasing irrigation, drought stress, and reducing yield (Ayas and Korukcu, 2010;Ayas, 2013;Porter et al, 1999). It seems that the reason for increasing dry matter percentage due to drought stress is to reduce the potential of water around the root and water deficit of the crop resulting in less water being directed to the tissues of the crop while the percentage of dry matter of the tubers increased (Bagheri et al, 2016).…”
Section: Percentage Of Dry Mattermentioning
confidence: 99%